Prognostic biomarkers in oral squamous cell carcinoma: current evidence and future directions - Brockmeyer, Phillipp (Frontiers in Oncology, 2025)
Oral squamous cell carcinoma (OSCC) exhibits significant prognostic heterogeneity. This has prompted extensive research into biomarkers that can predict clinical outcomes beyond conventional staging systems. This mini review summarizes findings from the existing literature to provide a comprehensive examination of the prognostic significance of malignancy and progression factors in OSCC, offering insights into future perspectives. There is clear evidence that molecular and protein-based biomarkers, in addition to established clinical and histopathological features, such as lymph node involvement, extranodal spread, and depth of invasion, strongly correlate with overall survival (OS), disease-free survival (DFS), and progression-free survival (PFS). Integrating different gene expression signatures, microRNA (miRNA) profiles, and changes in intracellular signaling pathways enables more differentiated risk stratification. Protein biomarkers such as cyclin D1, trophoblast cell surface antigen 2 (TROP2), urokinase-type plasminogen activator receptor (uPAR), and E-cadherin have been shown to provide clinically useful prognostic information. These results underscore the importance of incorporating biomarkers into individualized risk stratification to enhance personalized treatment regimens and outcomes for OSCC patients. Currently, however, established clinical and histopathological parameters, as well as a limited number of validated molecular profiles, remain the most reliable prognostic indicators. While identifying new biomarkers is promising, establishing standardized protocols and implementing careful prospective validation are essential to ensuring their seamless integration into standard clinical practice.